Preliminary results of floristic and vegetation surveys in three coastal humid areas in the Puglia region (southern Italy) - Di Pietro, Romeo; Dibitonto, Pietro; Garziano, Giuditta; Sciandrello, Saverio; Wagensommer, Robert P.; Medagli, Piero; Tomaselli, Valeria (Lazaroa, 2010)
This paper presents the preliminary results of an INTERREG project (III A Italy-Greece 2000-2006) concerning the improvement and management of common ecosystems. This project includes several humid areas located within the northwestern regions of Greece and the Italian region of Apulia. Owing to their similar paleogeographical and paleoclimatical accidents these areas exhibits several floristic and coenological peculiarities which lead to their inclusion in the Adriatic Province of the eastern Mediterranean biogeographical sub-region. The project involves making a GIS which permits the acquisition, processing, analysis, storage and feedback in graphic and alphanumeric form of the ecological data collected in three of the most significant coastal humid protected areas of the Apulia region, namely “Torre Guaceto”, “Le Cesine”, and “Saline di Punta della Contessa”. The importance of these humid areas can be inferred simply by observing the high number of Dir. 92/43/EEC habitats they contain. It is well-known that there are many negative factors which are currently threatening the Mediterranean retro-dunal ecosystems such as air and water pollution, urbanization, the impact of mass tourism, coastal erosion, lowering of the ground water table (etc.). These areas therefore urgently require a system of constant monitoring and, where necessary, actions to restore vegetation. All this demands a background of landscape knowledge concerning the small-scale vegetation pattern (actual heterogeneity) and the potential vegetation types (potential heterogeneity) as well. The three Apulian areas in the present study can easily be distinguished from each other from a floristic and coenological point of view. In addition to the slight (but probably crucial) differences in their physical environments, the existing diversity in the vegetation is more closely related to the minor and "unofficial" biogeographical boundaries prevailing in the part of the Apulian region and to the variation of the ecological optimum of several diagnostic species (Quercus ilex, Quercus calliprinos, Erica forskalii, Cladium mariscus, Plantago albicans, Limonium apulum....) than to the effective interruption of their distribution areas.